Recent Trends, Technical Concepts and Components of Computer-Assisted Orthopedic Surgery Systems: A Comprehensive Review - Kubicek, Jan; Tomanec, Filip; Cerny, Martin; Vilimek, Dominik; Kalova, Martina; Oczka, David (Sensors (Basel, Switzerland), 2019)
Computer-assisted orthopedic surgery (CAOS) systems have become one of the most important and challenging types of system in clinical orthopedics, as they enable precise treatment of musculoskeletal diseases, employing modern clinical navigation systems and surgical tools. This paper brings a comprehensive review of recent trends and possibilities of CAOS systems. There are three types of the surgical planning systems, including: systems based on the volumetric images (computer tomography (CT), magnetic resonance imaging (MRI) or ultrasound images), further systems utilize either 2D or 3D fluoroscopic images, and the last one utilizes the kinetic information about the joints and morphological information about the target bones. This complex review is focused on three fundamental aspects of CAOS systems: their essential components, types of CAOS systems, and mechanical tools used in CAOS systems. In this review, we also outline the possibilities for using ultrasound computer-assisted orthopedic surgery (UCAOS) systems as an alternative to conventionally used CAOS systems.
Keywords: medical image processing; chirurgie s pomocí počítače; fluoroscopic navigation; Tomography, X-Ray Computed; Robotics; ortopedické výkony; muskuloskeletální nemoci; Humans; zobrazování trojrozměrné; Musculoskeletal Diseases; Orthopedic Procedures; image-based navigation; imageless navigation; Imaging, Three-Dimensional; CAOS; počítačová rentgenová tomografie; Surgery, Computer-Assisted; robotika; lidé